Characterization of Epoxy Hybrid Composites Filled with Cellulose Fibers and Nano-SiC - Alamri, Hatem; Low, It Meng (John Wiley and Sons Inc, 2012)
Three different approaches have been applied and investigated to enhance the thermal and mechanical properties of epoxy resin. Epoxy system reinforced with either recycled cellulose fibers (RCF) or nanosilicon carbide (n-SiC) particles as well as with both RCF and n-SiC has been fabricated and investigated. The effect of RCF/n-SiC dispersion on the mechanical and thermal properties of these composites has been characterized. The fracture surface morphology and toughness mechanisms were investigated by scanning electron microscopy. The dispersion of n-SiC particles into epoxy nanocomposites was studied by synchrotron radiation diffraction and transmission electron microscopy. Results indicated that mechanical properties increased as a result of the addition of n-SiC. The presence of RCF layers significantly increased the mechanical properties of RCF/epoxy composites when compared with neat epoxy and its nanocomposites. The influence of the addition of n-SiC to RCF/epoxy composites in mechanical properties was found to be positive in toughness properties. At high temperatures, thermal stability of neat epoxy increased due to the presence of either n-SiC particles or RCF layers. However, the presence of RCF accelerated the thermal degradation of neat epoxy as well as the addition of n-SiC to RCF/epoxy samples increased the rate of the major thermal degradation.